Evaluation of inhibitory efficacy of plantaricin JK against NSP1 from SARS-CoV-2 by in silico methods - Manisha Mandal; Shyamapada Mandal (Aspects of Molecular Medicine)
SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), the causative agent of the COVID-19 pandemic, is still a cause of global concern, and therefore, safe and effective treatment is desperately needed. Bacteriocins produced by probiotic microorganisms displayed therapeutic potentiality against infectious diseases, including COVID-19. NSP1 (non-structural protein-1) of SARS-CoV-2 acts as a host translation inhibitor and reduces host immune function, thereby increasing viral pathogenicity and virulence. This information encouraged us to evaluate the inhibitory role of plantaricin JK (Pln-JK) against SARS-CoV-2 NSP1 using in silico methods. Herein, we used PatchMAN and CABS-dock webtools to perform molecular docking between SARS-CoV-2 NSP1 and Pln-JK, which generated NSP1-Pln-JK models. We used a peptide antiviral, peptide 5 (PEP5) as a reference. The top models (based on the lowest binding score and cluster density) of both systems were subjected to predict the binding affinity (ΔG, kcal/mol) and dissociation constant (KD, M) using PRODIGY. Pln-JK had excellent interaction with NSP1 displaying binding affinity of 9.1 kcal/mol and KD value of 2.1 × 10−7. The binding affinity and KD values for NSP1-PEP5 were −7.2 kcal/mol and 4.8 × 10−6 M (for PatchMan complex) and −5.9 kcal/mol and 4.8 × 10−5 M (for CABS-dock complex), respectively. HawkDock-based MM-GBSA binding free energies of CABS-dock and PatchMAN-generated complexes were −59.74 and −77.49 kcal/mol (for NSP1-Pln-JK) and −37.83 and −44.25 kcal/mol (for NSP1-PEP5), respectively. Further, molecular dynamic simulations-based MM-PBSA binding free energy confirmed NSP1-Pln-JK complex (−31.89 ± 0.91 kcal/mol) to be thermodynamically more stable than NSP1-PEP5 complex (−24.94 ± 0.6 kcal/mol). Pln-JK was predicted as non-allergic and non-toxic and thus emerged as a safe and effective molecule to combat SARS-CoV-2 infection. However, preclinical and clinical studies are needed before it can be considered as a prescription drug for the treatment of COVID-19.